A comparative study of nutritional values between chicken eggshells and cockle shells - Kadri, Nur Aqilah (2018)
Chicken eggshell and cockle shell were non-edible parts of food which disposed as waste. The content of egg chickens and cockle were edible and contains high protein which can provide energy to human. However, people not aware on nutritional values inside these shells. It contains high of calcium carbonate which beneficial to human, plants and animals. For human, calcium carbonate can be used as additional supplement of calcium in dietary human consumption. Calcium was important in bone formation and reduce the potential of getting osteoporosis. Also, calcium carbonate can act as pH stabilizer in soil. This project was carried out to compare the nutritional value between eggshells and cockle shells. The physical and chemical analysis were done using AOAC methods while calcium carbonate was detected by the titration test and using X-Ray Fluorescent (XRF). The trace elements in these shells were determined using X-Ray Fluorescent (XRF). For physical analysis, pH in cockle shells was 8.76 higher than eggshells 7.65. For colour analysis, after drying showed highest amount of calcium carbonate for both shells than others method. Amount of cockle shells after drying was 71.05 and eggshells was 68.71. Then, the calcium carbonate test has shown the same result which cockle shells content is higher than eggshells. Cockle shells has 90.84% and eggshells 75.83% of calcium carbonate. For moisture content, eggshells shows 1.14% higher than cockle shells 0.78%. Total ash of cockle shells was 97.67% while, eggshells was 95.35%. In eggshells, the total fat and protein content were 6.13% and 2.60% higher than cockle shells 0.24% and 0.28% respectively. The nutritional values of eggshells and cockle shells were determined by using AOAC methods. The X-ray fluorescent (XRF) was used to determine the elements that exist in shells and shows the calcium of cockle shells was 98.60% higher than eggshells 98.30%.